Exemptions Necessary, Justified, or Misguided? - Greenawalt, Kent (Harvard University Press, 2016)
Should laws apply to everyone, or should some people be exempt because of conflicting religious or moral convictions? Through a close study of several cases, from abortion to taxes, Kent Greenawalt demonstrates how to weigh competing values without losing sight of practical considerations like the difficulty of implementing a specific law